IMPLEMENTASI METODE TARTILA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA DI MIN 1 PROBOLINGGO - Sri Suciani; Feriska Listrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of the Tartila Method in improving the Qur'an reading proficiency of TPQ students at MIN 1 Probolinggo, located in Karanganyar Village, Paiton District, Probolinggo Regency. This research employed a qualitative approach using a case study design to gain an in-depth understanding of the learning process and its outcomes. Data were collected through observations, in-depth interviews, and documentation. The findings reveal that the Tartila Method is systematically implemented through several instructional stages, including the introduction of hijaiyah letters, sorogan-based learning, intensive guidance, and continuous monitoring of students' progress. The evaluation process consists of three levels: daily assessments, level promotion examinations, and graduation and completion evaluations. The implementation of the Tartila Method has contributed significantly to the improvement of students' Qur'an reading abilities, particularly in terms of reading fluency, accurate pronunciation of hijaiyah letters, and mastery of tajwid rules. Furthermore, the individualized and evaluative learning approach promotes effective and sustainable Qur'anic instruction. The success of the method is also supported by the active involvement of dedicated and patient teachers (ustadz and ustadzah) who consistently provide guidance throughout the learning process. Therefore, the Tartila Method can be considered an effective approach to enhancing Qur'an reading proficiency among TPQ students.